(untitled) (The Indonesian Accounting Review, 2022)
This study aims to explain and construct the concept of cost beyond the reasoning in mainstream accounting. This construction is carried out by redefning the cost based on the â€œperipheryâ€ case. I reference to the Nusantara paradigm, the four principles (kaidah) in building Siraman Gong Kiai Pradah methodology have been fulflled. Therefore, the method used has been out of the ordinary research methods. First, it prepares a â€œperipheryâ€ case to be investigated for the costs. Second, it draws the position closer to God by doing penances so that they are given instructions in reducing and classifying the data. Third, doing the charity. Fourth, it includes the â€œvalueâ€ of the â€œperipheryâ€ case in the new cost concept. Finally, this article proposes a change to the defnition of cost. Through the â€œperipheryâ€ case, the concept of cost transcends materialism. Cost is a number of expenses incurred, based on sincerity aimed at helping others in order to obtain the benefts both for the world and the hereafter by prioritizing the principle of mutual help.